2016
DOI: 10.1111/acps.12621
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of antipsychotic drugs in schizophrenia treatment: a real‐world observational study

Abstract: Both findings call for an international public health and drug agencies surveillance of 'real-world' antipsychotic medication to ensure the optimal choices in treatment guidelines for SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 37 publications
4
47
2
2
Order By: Relevance
“…In their large observational study, Vanasse et al showed that clozapine was more effective than other antipsychotics with regard to real-world clinical outcomes (i.e., suicide, hospitalization, and emergency department visit for mental disorders). 1 Their finding is in line with existing experimental and observational evidence that supports the current status of clozapine as the gold standard treatment for refractory schizophrenia.…”
supporting
confidence: 80%
“…In their large observational study, Vanasse et al showed that clozapine was more effective than other antipsychotics with regard to real-world clinical outcomes (i.e., suicide, hospitalization, and emergency department visit for mental disorders). 1 Their finding is in line with existing experimental and observational evidence that supports the current status of clozapine as the gold standard treatment for refractory schizophrenia.…”
supporting
confidence: 80%
“…In this issue of the Journal, Vanasse et al. report results on the comparative effectiveness of antipsychotic drugs in schizophrenia. The authors used administrative databases from Quebec province in Canada, which included more than 18 000 patients who started to use an antipsychotic from 1998 to 2005.…”
mentioning
confidence: 99%
“…Our results are in line with all previous large observational cohort studies (Tiihonen et al, Table 1 The mortality rates during monotherapy of specific antipsychotics among the prevalent and incident cohorts. 2006, 2011, 2012Baandrup et al, 2010, Crump et al, 2013: Vanasse et al, 2016 and meta-analyses on RCTs (Baxter et al, 2016;Khan et al, 2007Khan et al, , 2013. The lowest risk of death was observed during those time periods when patients used second generation LAIs, both in the prevalent and incident cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…Several observational studies on large unselected cohorts have shown that mortality is lower during use of antipsychotic compared with no use (Tiihonen et al, 2006(Tiihonen et al, , 2009(Tiihonen et al, , 2011(Tiihonen et al, , 2012Baandrup et al, 2010;Crump et al, 2013;Vanasse et al, 2016). However, these studies either did not control for survival bias or had short follow-up periods which made it difficult to evaluate the comparative effectiveness between specific antipsychotics.…”
mentioning
confidence: 99%